Implementasi Media Pembelajaran Interaktif Diorama Untuk Mengajarkan Keberagaman Dalam Pembelajaran PKN Sekolah Dasar - Nadia Fadillah Azhas; Regita Octaviani (Indonesian Journal Publisher, 2025)
Civic Education learning at the elementary school level is ideally designed to be interactive, fun, and effective, and able to encourage active student involvement in the learning process. In addition, learning must also provide sufficient space for students to develop their understanding of diversity in national and state life. This approach is in line with the basic principles of using interactive diorama media, which emphasizes the importance of adjusting the learning process to suit the individual needs of students who have different characters and learning styles. On this basis, researchers are interested in conducting a literature review on the application of interactive diorama media in teaching diversity values in Civics subjects in elementary schools. From the results of the literature analysis that has been carried out, several important findings were obtained: (1) interactive diorama media can be integrated with various relevant learning models in instilling diversity values; (2) the application of this media has been proven to improve students' understanding of the concept of diversity and encourage better learning outcomes; and (3) the learning approach using dioramas is very suitable to be applied at the elementary school level because it can adapt to the learning needs of students based on their profile, interests, talents, potential, and learning styles in understanding diversity issues